Patterns of postmeal insulin secretion in individuals with sulfonylurea-treated KCNJ11 neonatal diabetes show predominance of non-KATP-channel pathways - Pamela Bowman; Timothy J McDonald; Bridget A Knight; Sarah E Flanagan; Maria Leveridge; Steve R Spaull; Beverley M Shields; Suzanne Hammersley; Maggie H Shepherd; Robert C Andrews; Kashyap A Patel; Andrew T Hattersley (BMJ Open Diabetes Research & Care)
Objective Insulin secretion in sulfonylurea-treated KCNJ11 permanent neonatal diabetes mellitus (PNDM) is thought to be mediated predominantly through amplifying non-KATP-channel pathways such as incretins. Affected individuals report symptoms of postprandial hypoglycemia after eating protein/fat-rich foods. We aimed to assess the physiological response to carbohydrate and protein/fat in people with sulfonylurea-treated KCNJ11 PNDM.Research design and methods 5 adults with sulfonylurea-treated KCNJ11 PNDM and five age, sex and body mass index-matched controls without diabetes had a high-carbohydrate and high-protein/fat meal on two separate mornings. Insulin(i) and glucose(g) were measured at baseline then regularly over 4 hours after the meal. Total area under the curve (tAUC) for insulin and glucose was calculated over 4 hours and compared between meals in controls and KCNJ11 cases.Results In controls, glucose values after carbohydrate and protein/fat were similar (median glucose tAUC0-4h21.4 vs 19.7 mmol/L, p=0.08). In KCNJ11 cases glucose levels were higher after carbohydrate than after protein/fat (median glucose tAUC0-4h58.1 vs 31.3 mmol/L, p=0.04). These different glycemic responses reflected different patterns of insulin secretion: in controls, insulin secretion was greatly increased after carbohydrate versus protein/fat (median insulin tAUC0-4h727 vs 335 pmol/L, p=0.04), but in KCNJ11 cases insulin secretion was similar after carbohydrate and protein/fat (median insulin tAUC0-4h327 vs 378 pmol/L, p=0.50).Conclusions Individuals with sulfonylurea-treated KCNJ11 PNDM produce similar levels of insulin in response to both carbohydrate and protein/fat meals despite carbohydrate resulting in much higher glucose levels and protein/fat resulting in relatively low glucose levels. This suggests in an inability to modulate insulin secretion in response to glucose levels, consistent with a dependence on non-KATP pathways for insulin secretion.Trial registration number NCT02921906.